SKENARIO PENERAPAN KURIKULUM DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA MASA PANDEMI COVID-19 DI SMP AL HASIB PAKISJAJAR KECAMATAN PAKIS KABUPATEN MALANG - Miftahul Alifah Ardiyana; Ach. Faisol; Atika Zuhrotus Sufiyana (VICRATINA, 2021)
The scenario of implementing the curriculum in Islamic Religious Education learning during the Covid 19 pandemic is currently a new thing experienced by teachers and students at Hasib Pakis Middle School. The focus of this research is to discuss how to manage curriculum in Islamic Religious Education learning which includes planning, implementation, monitoring and evaluation. As well as supporting and inhibiting factors for curriculum implementation in Islamic religious education learning during the Covid 19 pandemic. Researchers used a qualitative approach using case study type research to achieve the research objectives. From this research, the researcher found the results of the research which included the preparation of a one-sheet RPP according to the recommendations of the government. For supporting factors, this study found that school management, the role of Islamic Education teachers, the roles of parents and students. The inhibiting factors of this study found that the conditions of facilities and infrastructure were less supportive, student saturation, and insufficient time allocation.